Abuse of Procedural Right in the Review of Judicial Acts in the Civil Process - A. N. Melnikova (Теоретическая и прикладная юриспруденция)
The purpose of this article is to analyze abuses of procedural right in civil and arbitrazh proceedings of the Russian Federation in the context of judicial review. The problem posed by the author is studied from “general” to “speciﬁc”: from the study of the potential for abuse of the right to appeal to the isolation and isolation of separate blocks of bad faith procedural behavior, typical for persons involved in the case. The author was able to identify four blocks of procedural abuse at the appeal stage: attempts to review judicial acts not in the manner prescribed by applicable law; circumvention of the prohibition to submit new evidence; inconsistent procedural conduct, as well as unreasonably prolonging the process of review. In addition, this article raises the question of the applicability of certain negative consequences for abusers in appellate and subsequent court proceedings. The article draws a conclusion about correlation of special norms (part 2 of article 111, part 5 of article 159 of the Commercial Procedure Code of the Russian Federation, article 99 of the Civil Procedure Code of the Russian Federation) with a basic general consequence of mala ﬁde procedural behaviour — refusal to satisfy claims of an abuser fully or partially.